Tuulten tanssi ; Kolmas kuu - Mandi, 1988-2008; Elo, Heikki, 1964-; Enqvist, Pentti; Heikkilä, Matti; Rhodes; Timonen, Marko, 1966-; Tyni, Seppo, 1954-; Välimäki, Minna; Willberg, Pepe, 1946- ([S.I.] : Mandi, 1994)
2 kappaletta.
Seppo Tyni (tuottaja).
Mandi (lauluääni). Tyni, Seppo (bassokitara, kitara). Rhodes (piano). Timonen, Marko (rummut). Heikkilä, Matti (lyömäsoittimet). Elo, Heikki (piano). Välimäki, Minna (käyrätorvi). Enqvist, Pentti (huilu). Willberg, Pepe (taustalaulu).
Keywords: popmusiikki